Identification and reduction of image artifacts in non–contrast‐enhanced velocity‐selective peripheral angiography at 3T. Issue 2 (26th August 2015) - Shin, Taehoon; Qin, Qin; Park, Jang‐Yeon; Crawford, Robert S.; Rajagopalan, Sanjay
Abstract : Purpose: To identify and reduce image artifacts in non–contrast‐enhanced velocity‐selective (VS) magnetization‐prepared peripheral MR angiography (MRA) at 3T. Methods: To avoid signal loss in the arteries, double and quadruple refocused VS excitation pulse sequences were designed that were robust to a wide range of B0 and B1 offset. To suppress stripe artifact and background signal variation, we successively applied two VS preparations with excitation profiles shifted by half the period of the stripes. VS‐MRA using single, double, and quadruple refocused VS preparations was tested in healthy subjects and a patient. Results: In the regions of large B0 and B1 offsets, arterial signal loss was yielded by single refocused VS preparation, but was avoided with double or quadruple refocused preparations. Compared with single VS preparation, the two consecutive preparations with shifted excitation profiles substantially reduced the stripe artifact and background signal variation, as demonstrated by increased mean and decreased standard deviation of relative contrast‐to‐noise ratio. The proposed VS‐MRA identified multilevel disease in the femoral arteries of the patient, as validated by digital subtraction angiography. Conclusion: Two multiple refocused VS magnetization preparations with shifted excitation profiles yield artifact‐free peripheral angiograms at 3T. Magn Reson Med 76:466–477, 2016. © 2015 Wiley Periodicals, Inc.